City Bias: Affordable Housing Accessibility Assessment—Evidence From 153 Prefectural Cities in China. (December 2022) - He, Chunyan; Li, Ding; Ma, Qiong; Yi, Daichun
This study explores the invisible bias quantification of urban governments in their affordable housing service delivery, which can accurately identify the deficiencies of affordable housing policy and alleviate homelessness, poverty, and inequality. We identified complicated eligibility criteria for public rental housing programs in 153 prefectural cities and constructed a public rental housing accessibility index for urban residents and migrants. We used the principal component analysis method; this study offers a new perspective to explore these disparities. We found distinct regional differences in local governments' behaviors and preferences regarding affordable housing. Cities' affordable housing provision for migrants is selective and mainly targets young and highly educated migrants. We suggest that local governments pay more attention to elderly migrant workers in affordable housing provision and build a comprehensive evaluation system to set reasonable access conditions to prioritize those with urgent housing needs.